Difficulties in the evaluation of solving algorithms - Dagienė, Valentina; Dagys, Viktoras (Lietuvos matematikos rinkinys, 2004)
The paper deals with the methods of algorithmical problems solving used in the Lithuanian Student Olympiads of Informatics, Young Programmers School, and comprehensive schools. Difficulties rising in the employment of the evaluation methods are discussed as well. The paper analyzes testing, which is the main method of algorithm evaluation, and the principles of the control tests drafting. The special attention is concentrated on the algorithm culture and the describing of the problems’ ideas.